Changes in Atlantic cod (Gadus morhua L.) sperm quality during the spawning season - Rouxel, Catherine; Suquet, Marc; Cosson, J; Severe, Armelle; Quemener, Loic; Fauvel, Christian (Aquaculture Research, 2008)
The biology of cod reproduction is well described in the scientific literature. However, sperm biology and spermatozoa management are poorly studied in this species. Because of its recent farming expansion, a better knowledge of cod gametes is becoming especially useful. This work aimed at establishing tools to study sperm biology in cod, and also investigated the existence of changes in cod sperm quality during the spawning period. We showed that sperm concentration could be assessed using spectrophotometry at 260 nm. Sperm motility significantly decreased after a 168-h storage at 4 degrees C. A 1:9 dilution of sperm in a non-activating medium (1/3 seawater and 2/3 freshwater, osmotic pressure: 360 mOsm kg(-1)) improved sperm storage. Sperm concentration, sperm velocity and storage capacity at 4 degrees C peaked during the medium period of the spawning season and then decreased to values close to those observed at the beginning of the reproductive period. The measured values of osmotic pressure, pH, protein, Na+, Cl- and Ca2+ concentrations of the seminal fluid were modified along the spawning period. Cell damage was noted at the end of the spawning period: local blebs were observed on the flagellum but also loops at its distal part. On the other hand, spermatocrit did not vary with the sampling date. In conclusion, cod sperm quality is modified during the spawning period, the highest-quality samples being collected during the medium part of this season.